Advancement in extraction of metals (Sb and As) from crystal glass by mechanochemical method and recovery of metal using ZnS nanoparticles synthesized from Cassia fistula plant extract. (August 2022) - Bukhari, Aysha; Ijaz, Irfan; Gilani, Ezaz; Nazir, Ammara; Zain, Hina; Saeed, Ramsha; Hussain, Sajjad; Naseer, Yasra; Aftab, Rizwana
Abstract: Due to the presence of antimony, lead, cadmium, arsenic, and nickel in crystal glass, glass waste disposal from crystal glass manufacturer are a health hazard. In the supply chain, recovering and recycling metals might reduce pollution. Antimony and arsenic were removed from waste crystal glass by using a novel mechanochemical method. Initially, crystal glass is crushed into powder for activation and then chemically treated with pentetic acid. pentetic acid was used as a chelating agent. By employing pentetic acid as a chelating agent and a mechanochemical method, we were able to remove 99.3 (%) mass of Sb and As heavy metals from crystal glass and first time in this work, nanoparticles were used to recovery the metals from waste glass. The maximum recovery of Sb and As was observed at 13 nm and a minimum at 95 nm, respectively. This increase in the recovery of metals with the decrease in size of nanoparticles was due to an increase in surface area. Graphical Abstract: ga1